A proposed mathematical model for the resolution of the Home Health Care (HHC) Nurse Scheduling Problem for Peritoneal Dialysis (PD) patients - BAHLOUL , Manel; MASMOUDI, Amina; REKIK, Ines (Revue Internationale des Sciences de Gestion, 2024)
Home HealthCare (HHC) are crucial for Peritoneal Dialysis (PD), ensuring patient’s satisfaction while minimizing both patient waiting times and the risks related to patients travel to hospitals. However, research in this area remains under-explored in Tunisia. This article introduces a mathematical model for nurse assignment and patients scheduling, aiming to optimize HHC for patients using PD in Tunisia. The proposed model aims to minimize the total start time of service for patients, thus demonstrating its applicability in the Tunisian context. To solve our model, we resort to two random instances since real data is not accessible. The results obtained highlight the model’s effectiveness in improving the quality of care and patient satisfaction, while also reducing costs and the risks associated with hospital travel.